Compliance management in research institutes: Boon or bane? - Katharina Pfeil; Sarah Necker; Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2023)
We examine the use and usefulness of systematic compliance management in research institutes using a survey of leaders of German research institutes and expert interviews. While only a quarter of the surveyed leaders report that they have an explicit compliance management system, they report to use a variety of other elements to increase compliance, e.g., an internal control system, systematic monitoring of the legal framework and risk management, training of employees, and whistleblowing systems. A large majority is convinced that compliance management is useful to ensure compliance with laws, internal rules, and ethical standards. According to the experts, compliance management is in the institutes' own interest. Experts argue that compliance management can provide the necessary framework for research autonomy, but also stress that it should not restrict freedom. They say that there is no one-size-fits-all approach to compliance in academia. Institutes should build on existing structures and establish a network on compliance issues.
Keywords: I23; C83; 330; Compliance Management; Misconduct; Research Institute; Survey; Expert Interview